PENGARUH LATIHAN INTERVAL ANAEROB DAN POWER LENGAN TERHADAP KECEPATAN RENANG 100 METER GAYA FRONT CRAWL - HERI PENDIANTO (Jurnal Ilmiah Spirit, 2010)
This research aims to find out (1) the effect difference of 25 meters and 50 meters distances anaerobic interval training on the Front Crawl style of 100-meter swimming speed increase, (2) the effect difference of 25 meters distance anaerobic interval training and the combination of 25-50 meters distance on the Front Crawl style of 100-meter swimming speed increase, (3) the effect difference of 50 meters distance anaerobic interval training and the combination of 25-50 meters distance on the Front Crawl style of 100-meter swimming speed increase, (4) the difference of Front Crawl style of 100-meter swimming speed between the swimmer with high arm power and the one with low arm power, and (5) the effect of interaction between the anaerobic interval training and the arm power on the Front Crawl style of 100-meter swimming speed. Â  This research employed an experimental method. The research design employed was a 3 x 2 factorial design. The subjects employed in the study were the male swimmers of Tirta Dharma and Almagari Surakarta swimmer association, as many as 36 swimmers. The sampling technique employed was purposive random sampling. Technique of analyzing data employed was ANAVA. Before running the 3 x 2 design ANAVA, the data analysis prerequisite test was done using the sample normality test (Lilliefors test with Î± = 0.05%) and variance homogeneity test (Bartlett test with Î± = 0.05%). Â  The conclusions of research are as follows: (1) There is a significant difference 25 meters and 50 meters distances anaerobic interval training in increasing the Front Crawl style of 100-meter swimming speed, (F0 = 11.4248 > Ft = 3.32). The effect of 25 meters distance anaerobic interval training is better then that of 50 meters distance anaerobic interval training, (2) There is a significant difference 25 meters and combination of 25-50 meters distances anaerobic interval training in increasing the Front Crawl style of 100-meter swimming speed, (F0 = 11.4248 > Ft = 3.32). The effect of 25 meters distance anaerobic interval training is better then that combination of 25-50 meters distance anaerobic interval training. (3) There is a significant difference 50 meters and combination of 25-50 meters distances anaerobic interval training in increasing the Front Crawl style of 100-meter swimming speed, (F0 = 11.4248 > Ft = 3.32). The effect of 50 meters distance anaerobic interval training is better then that combination of 25-50 meters distance anaerobic interval training. (4) there is a significant difference of Front Crawl style of 100-meter swimming speed between the swimmer with high arm power and the one with low arm power, (F0 = 5.1962 > Ft = 4.17). The effect of swimmer with high arm power is better then the one with low arm power, and (5) there is a significant the effect of interaction between the anaerobic interval learning and the arm power on the Front Crawl style of 100-meter swimming speed increase, (F0 = 7.0338 > Ft = 3.32). Â